Plasma lipid pattern and red cell membrane structure in β-thalassemia patients in Jakarta (Faculty of Medicine Universitas Indonesia, 2011)
Background: Over the last 10 years, we have investigated thalassemia patients in Jakarta to obtain a comprehensive picture of iron overload, oxidative stress, and cell damage. Methods: In blood samples from 15 transfusion-dependent patients (group T), 5 non-transfused patients (group N) and 10 controls (group C), plasma lipids and lipoproteins, lipid-soluble vitamin E, malondialdehyde (MDA) and thiol status were measured. Isolated eryhtrocyte membranes were investigated with electron paramagnetic resonance (EPR) spectroscopy using doxyl-stearic acid and maleimido-proxyl spin lables. Data were analyzed statistically with ANOVA. Results: Plasma triglycerides were higher and cholesterol levels were lower in thalassemic patients compared to controls. Vitamin E, group C: 21.8 vs T: 6.2 μmol/L) and reactive thiols (C: 144 vs. T: 61 μmol/L) were considerably lower in transfused patients, who exert clear signs of oxidative stress (MDA, C: 1.96 vs T: 9.2 μmol/L) and of tissue cell damage, i.e., high transaminases plasma levels. Non-transfused thalassemia patients have slight signs of oxidative stress, but no signifi cant indication of cell damage. Erythrocyte membrane parameters from EPR spectroscopy differ considerably between all groups. In transfusion-dependent patients the structure of the erythrocyte membrane and the gradients of polarity and fl uidity are destroyed in lipid domains; binding capacity of protein thiols in the membrane is lower and immobilized. Conclusion: In tranfusion-dependent thalassemic patients, plasma lipid pattern and oxidative stress are associated with structural damage of isolated erythrocyte membranes as measured by EPR spectroscopy with lipid and protein-thiol spin labels. (Med J Indones 2011; 20:178-84)